Prehispanical architecture of Lima between XI and XV centuries: The cases of the conservation of Mateo Salado's A Pyramid - Soto Medina, Mirna (2018)
Since year 1000 of the Christian era to the late pre-Hispanic period, the Yschma culture flourished in Lima. Its heritage are numerous huacas or pre-Hispanic buildings, which are characterized by soil as the main building material, from mortar to lay stones to large blocks and plasters. Historical testimony of this period are archaeological sites like the Maranga Complex, located in the current Parque de las Leyendas, the Catholic University and the University of San Marcos, and others like Mateo Salado, Huaca La Luz, Huantille, Huantinamarca, San Borja, La Merced and many more. These buildings have been seriously affected by the passage of time, earthquakes and the advance of modernity. This essay presents the constructive - structural description of the archaeological complex Mateo Salado (1532 AD - 1100 AD), and the conservation and consolidation work performed in 2007 in the pyramid A, developed by an interdisciplinary team that integrated archeology, conservation and structural engineering, which was oriented by the concept of respect for authenticity, deep knowledge of the constructive material, structural safety and intervention with minimal impact on the cultural value.